2021
DOI: 10.1111/ibi.12992
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences of the Ortolan Bunting (Emberiza hortulana) in its prime wintering grounds, the cereal‐dominated Ethiopian Highlands

Abstract: Agricultural intensification and land‐use changes are major factors impacting farmland biodiversity. The Ortolan Bunting Emberiza hortulana is the long‐distance trans‐Saharan migratory passerine that has undergone the most dramatic decline among all European farmland birds. The factors responsible for this decline may originate from the breeding grounds, migration stopovers and/or overwintering quarters. Very little is known about conditions on the species' wintering grounds, but a recent study has highlighted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, current studies are heavily biased toward the breeding grounds and knowledge of what is happening on the nonbreeding grounds is largely missing (Marra et al, 2015). Even studies that assessed the causes of decline of Afro-Palearctic migrants in their wintering grounds focused primarily on remote sensing techniques (Beresford et al, 2019) despite that habitat preferences of landbirds are often only detectable by quantifying finescaled habitat characteristics necessitating ground-based fieldwork in Africa (Marcacci et al, 2020(Marcacci et al, , 2022Gremion et al, 2022; see step 3 in Box 1). We therefore strongly encourage more ground-based studies in the identified geographic regions at the relevant stages of the targeted species' annual cycles in order to determine the potential threats and drivers of population declines and how to mitigate them.…”
Section: Step 3: Identifying Threats and Conservation Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, current studies are heavily biased toward the breeding grounds and knowledge of what is happening on the nonbreeding grounds is largely missing (Marra et al, 2015). Even studies that assessed the causes of decline of Afro-Palearctic migrants in their wintering grounds focused primarily on remote sensing techniques (Beresford et al, 2019) despite that habitat preferences of landbirds are often only detectable by quantifying finescaled habitat characteristics necessitating ground-based fieldwork in Africa (Marcacci et al, 2020(Marcacci et al, , 2022Gremion et al, 2022; see step 3 in Box 1). We therefore strongly encourage more ground-based studies in the identified geographic regions at the relevant stages of the targeted species' annual cycles in order to determine the potential threats and drivers of population declines and how to mitigate them.…”
Section: Step 3: Identifying Threats and Conservation Challengesmentioning
confidence: 99%
“…The recent tracking data demonstrating that the majority of the world population overwinters in the Ethiopian Highlands calls for concerted research activities in this seemingly important habitat. Gremion et al (2022) conducted a field study in Ethiopia to investigate the habitat preferences of the overwintering Ortolan Buntings. They demonstrated the importance of small-scale agriculture with traditionally managed cereal-grain fields interspersed with seminatural habitats for the conservation of the species.…”
Section: A Case Study: the Ortolan Buntingmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, long-distant migrants among farmland birds are particularly threatened as they are also subject to further threats outside their breeding ranges (e.g. Bairlein 2016, Gremion et al 2022).…”
Section: Introductionmentioning
confidence: 99%